2014
DOI: 10.1530/eje-13-0642
|View full text |Cite
|
Sign up to set email alerts
|

The prevalence of IgG4-related hypophysitis in 170 consecutive patients with hypopituitarism and/or central diabetes insipidus and review of the literature

Abstract: Objective: The prevalence and clinical characteristics of IgG4-related hypophysitis remain unclear due to the limited number of case reports. Therefore, in this study, we screened consecutive outpatients with hypopituitarism and/or diabetes insipidus (DI) to estimate its prevalence. Methods: A total of 170 consecutive outpatients with hypopituitarism and/or central DI were screened at Kobe University Hospital for detecting IgG4-related hypophysitis by pituitary magnetic resonance imaging, measuring serum IgG4 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
70
4
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 115 publications
(81 citation statements)
references
References 41 publications
(44 reference statements)
6
70
4
1
Order By: Relevance
“…Recent work has identified an IgG4-related plasmacytic secondary hypophysitis variant, often in patients with IgG4 systemic disease [3,14]. Relatively few case reports have been published since first descriptions based on clinical suspicion in 2004 [15], and pathological confirmation in 2007 [16], however a recent review suggests that its incidence may be significantly underreported [17].…”
Section: Introductionmentioning
confidence: 99%
“…Recent work has identified an IgG4-related plasmacytic secondary hypophysitis variant, often in patients with IgG4 systemic disease [3,14]. Relatively few case reports have been published since first descriptions based on clinical suspicion in 2004 [15], and pathological confirmation in 2007 [16], however a recent review suggests that its incidence may be significantly underreported [17].…”
Section: Introductionmentioning
confidence: 99%
“…To our knowledge, there have been only 29 such cases reported so far [4]. The first case of IgG4-related hypophysitis was reported in Japan in the year 2000 [5].…”
Section: Discussionmentioning
confidence: 99%
“…In the review by Bando et al [4] only 14% of the patients solely exhibited hypophysitis, which was diagnosed by histopathology. In 2011 Leporati et al [9] suggested five criteria to diagnose IgG4-related hypophysitis (Table III).…”
Section: Discussionmentioning
confidence: 99%
“…Hashimoto encephalopathy was found to be associated with high serum and intrathecal IgG4 levels in a case report [59]. IgG4-related hypophysitis has been the subject of case reports and a case series [60]. …”
Section: Other Endocrine Associationsmentioning
confidence: 99%